Az eunuch visszaherélése: Olty Péter Hopkins-fordításairól - Horváth, Imre Olivér (Studia Litteraria, 2024)
The paper compares Péter Olty’s translations of Gerard Manley Hopkins’s poetry with a selection published in the Lyra Mundi series by Európa Kiadó in 1985. Olty’s newly published collection, Istenáram (Kalligram, 2023) strives to preserve the particularities of Hopkins’s enigmatic and eccentric language. These include, among other things, sprung rhythm and consonant chiming, a vocabulary rich in neologisms, archaisms, and dialect words, and a stretching of grammatical conventions. These attributes make Hopkins’s poetry unique, highly enjoyable, and also challenging for readers. Whereas the translators of the Lyra Mundi selection toned down the peculiar language of the originals in favor of readability, Olty’s translations retain Hopkins’s distinctive style.